Analisis Pelaksanaan Praktikum dan Kelengkapan Sarana Prasarana Laboratorium Biologi di SMA Negeri Kota Padangsdimpuan - Lia Junita Harahap (Institut Agama Islam Negeri, 2022)
Practicum has an important role in learning science, especially biology. The continuity of the practicum can be supported by the existence of laboratory facilities. This study aims to determine the description of the implementation of biology practicum and the completeness of laboratory infrastructure at Senior High School State of Padangsidimpuan. The research method in this study is quantitative descriptive with 97 students and 11 biology teachers as the sample. Collecting data using questionnaires and observations. Questionnaires for teachers and students were used to determine the implementation of the practicum and observations in the laboratory were used to determine the completeness of the biology laboratory infrastructure. Based on data analysis, the average implementation of biology practicum and completeness of biology laboratory is 74.51 and 72.06 respectively.